The Ukrainian Peasant Home : Space Domestication - Shostok, Natalia (Ethnologies, 1995)
The paper deals with the traditional Ukrainian home of Central Ukraine at the beginning of the twentieth century. The domestication of the home is considered to consist of two different stages: physical detachment of the site from the outer world and its further differentiation. The formation of the inner space-cooking area, sleeping area, holy corner, household work area, and guest area-depended on the belief that the inner space of the peasant home was inhabited by humans as well as supernatural entities: pagan spirits, homeguards and deceased ancestors, and Christian saints.